Optimasi Augmented Reality Sebagai Media Pembelajaran Interaktif Alat Musik Gamelan Jawa Tengah - Sri Radhika Wisnu Wardani; Yusmedi Nurfaizal; Wiga Maulana Baihaqi (STMIK Sumedang, 2021)
Education is basically a process of maturing students through the development of abilities and skills that exist in themselves so that they can be of quality so that the abilities and skills they have can play a role in building themselves and the surrounding community. One of the subjects that practice the abilities and skills of students is the Cultural Arts. Art and culture is a material taught in middle school. At SMP N 1 Sumpiuh, Arts and Culture teaches the traditional music of Central Java, Gamelan. So far the supporting media used by teachers to teach are still inadequate because of the limited amount of Gamelan. This is considered less effective in teaching Gamelan practice. The purpose of this study is to create an interactive media for learning the musical instrument of Gamelan in Central Java in the form of an Augmented Reality-based application to help the introduction of Gamelan in Cultural Arts material. The system development method used is the MDLC method. From the results of the beta test using a questionnaire against 15 respondents and produced a value of 89.33% with the category of strongly agree. The results of this study are augmented reality optimization as an innovative learning media for Central Java gamelan music instruments